Separation optimization and quantitative analysis of phytoestrogens employing reverse-phase high-performance liquid chromatography with UV-VIS detection. Issue 17 (14th December 2021) - Payette, Michael; Lima, Marta R. M.; Coleman, William M.; Ashraf-Khorassani, Mehdi
Abstract: The effect of different acidic modifiers on the separation of seven selected phytoestrogens by reverse-phase high-performance liquid chromatography has been described. Variation in the hydrocarbon chain length of organic acids as represented by acetic acid, propanoic acid, iso-butyric acid, and n-butyric acid as additives to the mobile phase had minimal effect on the separation of phytoestrogens but notably reduced sample turnaround times relative to the turnaround time linked with formic acid. Two different C18 columns were evaluated in attempts of optimize the phytoestrogen separations. Formic acid as a modifier in the mobile phase and an Atlantis C18 column provided the best overall separation at optimum gradient conditions. A higher acid concentration in the mobile phase did not improve the phytoestrogen separation. Higher column temperature (40 °C) provided an improved separation. Finally, the optimized method was used to quantify different phytoestrogens in selected different botanical samples. For this purpose, both internal and external standard methods were compared to obtain the quantitative results. Graphical Abstract: UF0001